Financial Literacy in Generation Z (Case Study on Students of SMA Panca Budi Medan) - Geby Citra Ananda; Zuhri Ramadhan (International Journal of Management, Economic and Accounting, 2024)
In the era of 2020 there are many offers to make purchases easily and quickly for generation Z, proper financial management is needed for generation Z today, so as not to be tied to consumerism. This research is the result of financial literacy training from students of SMA Panca Budi Medan, researchers want to know if there are differences in understanding and application of financial literacy after attending this financial literacy training. This financial literacy training is carried out for 2 months and is systemized, where students are assessed for their understanding and application. This study used a non-parametric paired t-test. This research data was taken using questionnaires distributed before and after training. Students were given a financial literacy questionnaire according to Chen and Volpe (1998). The results of this study indicate that after participating in financial literacy training, students' understanding of financial literacy does not experience differences with before training, but on average there is an increase in understanding. In the application of financial literacy there is a difference before and after financial literacy training.